Prior calculation of the accuracy of monitoring of cultural heritage objects using UAVs and laser scanning - Chumak, Olga; Gorkovchuk, Julia (Geodesy and Cartography, 2023)
In the last few years, intensive measures have been taken to monitor and inventory the cultural heritage of Ukraine. An important aspect is the preservation of such objects and their transmission to future generations. It is important to use such a methodology and technology when performing monitoring works, which in the future will make it possible to perform a number of other tasks, in relation to a certain specific object, based on previously obtained data. Therefore, this paper proposes a method of cultural heritage monitoring using UAV-filming. The work examines the methods of monitoring cultural heritage objects and presents an a priori assessment of the accuracy of monitoring of cultural heritage by means of UAV photography and laser scanning. The work focuses on the fact that the monitoring of cultural heritage sites should be carried out precisely with the help of modern filming methods, which have a number of advantages compared to traditional methods. The reliability of the proposed methods is presented and substantiated by calculating an a priori estimate of the accuracy of potential results.